J.A. Schumpeter and the theory of economic evolution (One hundred years beyond the theory of economic development) - Stan Metcalfe (Max Planck Institute of Economics, 2012)
The centennial of the publication of Schumpeter's Theory of Economic Development is an occasion to look back in appraisal and an opportunity to look forward in anticipation to consider anew the challenges that remain unfulfilled for Schumpeterians. Along with Marx and Marshall, Schumpeter's great achievement was to formulate an evolutionary, open system perspective on modern capitalism, to explain why it could never be at rest and to link its emergent properties to the capacity to change from within. In terms of appraisal, I shall focus on three aspects of Schumpeter's scheme: the link between knowledge, enterprise and the meaning to be attributed to a knowledge economy, the nature of the competitive process in the presence of innovation, and the transient, out of equilibrium nature of all economic arrangements. In looking forward, I shall consider what is missing from evolutionary economic dynamics, pointing to the role of factor markets in the competitive process, the significance of differences in firm's investment strategies and the fine grained nature of competition in markets where differences in the qualities of goods and services matter, and, lastly, on the evolutionary dimensions of international competition. Two lessons are particularly pertinent to advancing the Schumpeterian enterprise. First, that the familiar one-dimensional models of economic evolution are useful but incomplete. Secondly, that, while much evolutionary thinking has naturally focused on the connection between the micro and the meso, we need also to consider the connection between the meso and the macro and in so doing connect to rich literatures in the field of economic growth and development.
Keywords: 330; Evolutionsökonomik; Schumpeterismus; Dogmengeschichte